Why is the inheritance tax so controversial? - Beckert, J (2008)
Inheritance taxes have rarely ever contributed more than two per cent to the budget of any modern state. Nevertheless, in the twentieth and early twenty-first centuries some of the most vocal conflicts over taxation took place over inheritance taxes. This holds true for the United States as well as for many European countries. In the United States, estate taxation has been a topic of controversial political debate and will remain on the political agenda, at least until a decision has been made on what will happen to the tax after 2010. This policy brief addresses the question of why inheritance taxation is such a deeply controversial issue, arguing that the profoundly contentious character of this tax cannot be attributed solely to the material position of the testator and his or her heirs. Instead, these conflicts have much deeper roots in the way this tax relates to the normative fabric of societies. The brief distinguishes four different principles that legitimize the inter-generational transfer of wealth: the family principle, the equality of opportunity principle, the social justice principle, and the community principle.